Digital skills and evaluation of teaching performance at I.E Fe y Alegría N°23. Villa María Del Triunfo. Lima - Nuñez Marcos, Liz Gabriela (2025)
After the pandemic, the need for teachers with advanced digital skills has become increasingly evident in Peruvian education, especially in public education, so our studies aim to determine whether there are relationships between digital competence and academic performances. IE Fe y Alegría N.23 Villa María del Triunfo. To do this, we use quantitative methods, hypothetico-deductive, ordinal and cross-level methods. The design is descriptively and inferentially relevant. Surveys validated by three experts are completed, and their reliability was confirmed using Cronbach's alpha, providing a high degree of reliability for the two variables studied. Descriptive statistics and Spearman's Rho coefficient were used for data analysis for hypothesis testing. Various aspects of digital competencies are explored and cover areas such as technologies, pedagogies, communications and research management. When evaluating the work of teachers, factors such as actively involving students in education, evaluating their progress, promoting environments characterized by compliance and empathy, and effective management of student behavior are taken into account. The results show that there is a significant positive correlation between teachers' numerical skills and their performance ratings, as shown by the coefficient r=0.193 The correlation is very low, p=0.000. This result led us to corroborate the alternative hypothesis and reject the null hypothesis.